Determinants and consequences of failure of linkage to antiretroviral therapy at primary care level in Blantyre, Malawi: a prospective cohort study. - Peter MacPherson; Elizabeth L Corbett; Simon D Makombe; Joep J van Oosterhout; Eddie Manda; Augustine T Choko; Deus Thindwa; S Bertel Squire; Gillian H Mann; David G Lalloo (PLoS ONE)
Background Poor rates of linkage from HIV diagnosis to ART initiation are a major barrier to universal coverage of ART in sub-Saharan Africa, with reasons for failure poorly understood. In the first study of this kind at primary care level, we investigated the pathway to care in the Malawian National Programme, one of the strongest in Africa. Methods and findings A prospective cohort study was undertaken at two primary care clinics in Blantyre, Malawi. Newly diagnosed HIV-positive adults (>15 years) were followed for 6-months to assess completion of eligibility assessments, initiation of ART and death. Two hundred and eighty participants were followed for 82.6 patient-years. ART eligibility assessments were problematic: only 134 (47.9%) received same day WHO staging and 121 (53.2%) completed assessments by 6-months. Completion of CD4 measurement (stage 1/2 only) was 81/153 (52.9%). By 6-months, 87/280 (31.1%) had initiated ART with higher uptake in participants who were ART eligible (68/91, 74.7%), and among participants who received same-day staging (52/134 [38.8%] vs. 35/146 [24.0%] p = 0.007). Non-completion of ART eligibility assessments (adjusted hazard ratio: 0.11, 95% CI: 0.06-0.21) was associated with failure to initiate ART. Retention in pre-ART care for non-ART initiators was low (55/193 [28.5%]). Of the 15 (5.4%) deaths, 11 (73.3%) occurred after ART initiation. Conclusions Although uptake of ART was high and prompt for patients with known eligibility, there was frequent failure to complete eligibility assessment and poor retention in pre-ART care. HIV care programmes should urgently evaluate the way patients are linked to ART. In particular, there is a critical need for simplified, same-day ART eligibility assessments, reduced requirements for hospital visits, and active defaulter follow-up.